Analisis Aritmia (Gangguan Irama Jantung) Menerapkan Metode Certainty Factor - Masyuni Hutasuhut; Tugiono Tugiono; Asyahri Hadi Nasyuha (STMIK Budi Darma, 2021)
The heart is one of the most important organs for humans that functions to pump oxygenated blood, the heart can experience problems, one of which is arrhythmia, arrhythmia is a heart rhythm disorder or pattern of rapid changes from a normal heart rate. Heart rhythm disturbances (arrhythmias) are patterns of rapid change from the normal heart rate. This becomes a problem when not handled properly and correctly because it can cause disruption of the heart's function, even in more severe cases it can cause sudden death. An expert system is one of the artificial intelligence of humans that studies how an expert thinks in solving a problem, making decisions or drawing conclusions from a number of facts. An expert system is a system that adopts the expertise of an expert that can be used to overcome certain problems, one of which is diagnosing arrhythmias. This study applies Certainty Factor analysis which can provide additional knowledge to the public, especially knowledge on heart disease. So that arrhythmia analysis with this certainty factor method can be applied to a system that helps the general public in preventing and overcoming heart rhythm disorders